Hiperbilirrubinemia y Factores de Riesgo en Neonatos atendidos en el Hospital de Apoyo Chepén - La Libertad. 2018 - 2019 - Tongo Pizarro, María Bertha (2020)
The objective was to determine the risk factors of neonatal hyperbilirubinemia in the Pediatric-Neonatology Service of the Chepén Health Support Hospital. The research is descriptive, observational, retrospective, cross-sectional and quantitative, conducted between 2018 to June 2019. The sample was 312 neonatal patients with hyperbilirubinemia, out of a total of 1,651 newborns. The results obtained are related to the prevalence of neonatal hyperbilirubinemia in the Pediatric-Neonatology Service of the Chepén Health Support Hospital. The risk factors for neonatal hyperbilirubinemia are: sex of the newborn, siblings with a history of jaundice, presence of urinary tract infection (UTI), application of oxytocin, blood incompatibility, presence of cephalohematoma, gestational age, neonatal sepsis, and dystrophic delivery. Family risk factors, in order of prevalence are: UTI in pregnant women, application of oxytocin, siblings with a history of jaundice and blood incompatibility. The newborn's own risk factors, in order of prevalence, are: dystocic delivery, neonatal sepsis, gestational age and presence of cephalohematoma.